Laws Pertaining to Right to Privacy at the International Scenario: Enforcing Right to Privacy in the International Scenario: Indian Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2016)
“Everyone has the right to respect for his private and family life, hishome and his correspondence; there shall be no interference by a publicauthority except such as is in accordance with law and is necessary in ademocratic society in the interests of national security, public safety or theeconomic well-being of the country, for the protection of health or morals orfor the protection of the rights and freedoms of others.” India is a signatory to the International Covenant on Civil andPolitical Rights and Universal Declaration of Human Rights, 1948, India has theobligation to enforce these rights. In the lack of enabling legislation, theICCPR can have the legal force as the other laws in India. And the UDHR is amere declaration, and it does not have the legal force. But the courts haveused provisions of ICCPR and UDHR to make its argument stronger; and also inorder to make realize the government about its obligation towards its citizenand towards international instruments.